To the question of cooperation of the banking sector with the small and medium-sized enterprises: the modern state, foreign experience and ways of improvenient - Shmatkovska, Tetiana О.; Шматковська, Тетяна Олександрівна (Дніпропетровський державний аграрно-економічний університет, 2016)
The subject of the article is the problem of organization of bank crediting by enterprises of small and medium businesses in Ukraine. Based on the studies and analysis of native experience, the recommendations for improvement and intensification of situation with lending to small and medium businesses have been provided. In order to ensure the active participation of banking system of the country in forming investing resources of the enterprises of small and medium businesses, one should improve the mechanism of implementation of this program by providing an optimal combination of legislative, administrative, regulatory and economic instruments of influence on the credit activity of commercial banks to ensure simplification of conditions for an access for the enterprises of small and medium businesses to credit resources of banking system. For the development of the Ukrainian economy and small and medium businesses in general, the necessary reduction in the tax burden for newly established small businesses, as well as creating favourable conditions for them to taking funds. Предметом статті є проблема організації банківського кредитування підприємств малого і середнього бізнесу в Україні. На підставі вивчення та аналізу вітчизняного і зарубіжного досвіду, надано рекомендації для забезпечення покращення та активізації ситуації в сфері кредитування малого та середнього бізнесу. Обґрунтовано, що з метою забезпечення стимулювання участі банківської системи країни у формуванні інвестиційних ресурсів підприємств малого і середнього бізнесу, необхідно удосконалити безпосередньо механізм реалізації цієї програми, а саме забезпечити оптимальне поєднання законодавчих, адміністративно-регулятивних і економічних важелів впливу на кредитну активність комерційних банків з метою забезпечення спрощення умов доступу підприємств малого і середнього бізнесу до кредитних ресурсів банківської системи. Для розвитку української економіки та суб’єктів малого і середнього бізнесу в цілому, необхідне зменшення податкового навантаження для новостворених суб’єктів малого бізнесу, а також створення для них сприятливих умов взяття кредитних коштів.
До питання співробітництва банківського сектору з підприємствами малого та середнього бізнесу: сучасний стан, зарубіжний досвід та шляхи покращення
Keywords: small and medium business; investments; crediting; refinancing; commercial bank; малий та середній бізнес; інвестиції; кредитування; рефінансування; комерційний банк